2020
DOI: 10.3390/w12113287
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption Selectivity of Short and Long Per- and Polyfluoroalkyl Substances (PFASs) from Surface Water Using Powder-Activated Carbon

Abstract: Nine per- and polyfluoroalkyl substances (PFASs), including six perfluoroalkyl carboxylic acids (PFCAs) and three perfluoroalkyl sulfonic acids (PFSAs), were tested to find their adsorption selectivity from surface water and the feasibility of the powder activated carbon (PAC) process between the perchlorination and coagulation processes by operating parameters such as mixing intensity, dosage, contact time, initial pH, and concentration of perchlorination. The removal efficiency of four types of PAC revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Specifically, PFOS had a complete breakthrough at 400 PV, much later than its analogous PFNA, which showed a complete breakthrough at 234 PV. Stronger sorption of PFSAs than PFCAs has similarly been reported before for sorption to soils (Campos Pereira et al, 2018) and activated carbons (Park et al, 2020;Son et al, 2020). This can be explained by the stronger hydrophobicity of PFSAs than their analogous PFCAs due to the larger size of the sulphonate moiety (Higgins and Luthy, 2006).…”
Section: Column Experimentssupporting
confidence: 66%
“…Specifically, PFOS had a complete breakthrough at 400 PV, much later than its analogous PFNA, which showed a complete breakthrough at 234 PV. Stronger sorption of PFSAs than PFCAs has similarly been reported before for sorption to soils (Campos Pereira et al, 2018) and activated carbons (Park et al, 2020;Son et al, 2020). This can be explained by the stronger hydrophobicity of PFSAs than their analogous PFCAs due to the larger size of the sulphonate moiety (Higgins and Luthy, 2006).…”
Section: Column Experimentssupporting
confidence: 66%
“…Mesoporous hafnium oxide, a group IV transition metal oxide, is an attractive PFOA adsorption candidate. Mesoporous materials lead to increased PFOA adsorption as the diameter of PFOA is about 2 nm ( Xiang et al., 2018 ), and previous work has shown that microporous materials (<2 nm) are not ideal for PFOA adsorption ( Son et al., 2020 ). The high thermal (700°C) and chemical stability (active sites on the surface) of MHO ceramic, results from its highly coordinated hafnium.…”
Section: Introductionmentioning
confidence: 99%
“…It also addresses factors affecting PFAS removal via membrane filtration and delineates research gaps and key future research directions. In recent years, a growing number of studies have addressed the environmental occurrence, fate, and transport of PFAS in potable water and wastewater treatment plants, as well as varying treatment approaches [2,[27][28][29][30][31]. Therefore, it is necessary to systematically review and critically analyze the state of knowledge and determine research gaps for suitable and economically viable technology leading to PFAS removal from water.…”
Section: Background On Pfasmentioning
confidence: 99%